2004-6-16 to 2014-8-15: The birth and death of a work by Gu Dexin. (1st June 2016) - Moy, Sara A.
Abstract : Conservators who work with contemporary materials are experiencing a paradigm shift that affects not only their role, but also the decision-making process associated with each unique work. Importantly, such actions sometimes contradict established preservation doctrine. This paper describes the challenging preservation efforts associated with a large-scale sculpture/installation produced in 2004 by Gu Dexin. Those efforts contradicted many of the standards and ethics of conservation, particularly considerations related to compromising the life of a given work. Ultimately, the decision made in this case led to the demise of that object. This paper will include information obtained from the various stakeholders — including the donor and the artist — and a compendium of the exhaustive considerations that facilitated the final decision.